Analysis Soft System Methodology of Digital MSME Development in DKI Jakarta - Aditya, Ricky; Z.Rusfian, Effy; Fitriati, Rachma (Indonesian Journal of Islamic Economics and Business, 2024)
This study employs the Soft System Methodology (SSM) to analyze and develop strategies for the digitalization of Micro, Small, and Medium Enterprises (MSMEs) in DKI Jakarta. Given the significant role of MSMEs in Indonesia's economy, contributing 61% to the Gross Domestic Product and employing 97% of the workforce, their integration into the digital landscape is crucial. The research highlights existing challenges, such as limited digital literacy, constrained access to capital, and inadequate product standardization, and identifies opportunities for enhancing MSME competitiveness through digital tools. By applying SSM, the research constructs a conceptual model to address these challenges, emphasizing stakeholder collaboration among government, academia, and the private sector. The findings offer a strategic framework for effective digital transformation, aiming to improve efficiency and foster sustainable economic growth.